Inhibition of PRMT5 by market drugs as a novel cancer therapeutic avenue - Lakshmi Prabhu; Matthew Martin; Lan Chen; Özlem Demir; Jiamin Jin; Xiumei Huang; Aishat Motolani; Mengyao Sun; Guanglong Jiang; Harikrishna Nakshatri; Melissa L. Fishel; Steven Sun; et al. (Genes and Diseases, 2023)
Market drugs, such as Food and Drug Administration (FDA) or European Medicines Agency (EMA)-approved drugs for specific indications provide opportunities for repurposing for newer therapeutics. This potentially saves resources invested in clinical trials that verify drug safety and tolerance in humans prior to alternative indication approval. Protein arginine methyltransferase 5 (PRMT5) overexpression has been linked to promoting the tumor phenotype in several cancers, including pancreatic ductal adenocarcinoma (PDAC), colorectal cancer (CRC), and breast cancer (BC), making PRMT5 an important target for cancer therapy. Previously, we showed that PRMT5-mediated methylation of the nuclear factor (NF)-κB, partially contributes to its constitutive activation observed in cancers. In this study, we utilized an AlphaLISA-based high-throughput screening method adapted in our lab, and identified one FDA-approved drug, Candesartan cilexetil (Can, used in hypertension treatment) and one EMA-approved drug, Cloperastine hydrochloride (Clo, used in cough treatment) that had significant PRMT5-inhibitory activity, and their anti-tumor properties were validated using cancer phenotypic assays in vitro. Furthermore, PRMT5 selective inhibition of methyltransferase activity was confirmed by reduction of both NF-κB methylation and its subsequent activation upon drug treatment. Using in silico prediction, we identified critical residues on PRMT5 targeted by these drugs that may interfere with its enzymatic activity. Finally, Clo and Can treatment have exhibited marked reduction in tumor growth in vivo. Overall, we provide basis for pursuing repurposing Clo and Can as anti-PRMT5 cancer therapies. Our study offers potential safe and fast repurposing of previously unknown PRMT5 inhibitors into clinical practice.